2007
DOI: 10.1063/1.2770659
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature spin-oriented photocurrent under near-infrared irradiation and comparison of optical means with Shubnikov de-Haas measurements in AlxGa1−xN∕GaN heterostructures

Abstract: The admixture of linear and circular photogalvanic effects and (CPGEs) in AlxGa1−xN∕GaN heterostructures has been investigated quantitatively by near-infrared irradiation at room temperature. The spin-based photocurrent that the authors have observed solidly indicates the sizable spin-orbital interaction of the two-dimensional electron gas in the heterostructures. Further analysis shows consistency between studies by optical and magnetic (Shubnikov de-Haas) measurements on the spin-orbital coupling effects amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Therefore, all the linear in k terms are of the Rashba-type, 12 which makes them indistinguishable in experiments. Indeed, experiments revealed that the spin-orbit coupling is dominated by the Rashba-type spin-orbit coupling, where no effect that signals spin-orbit coupling of the form of (k x σ x − k y σ y ) was observed [247,[256][257][258][259][260]. The measured Rashba parameter lies in the range of 0.6 to 8 × 10 −12 eV m various conditions [251][252][253][254][261][262][263][264][265][266][267][268].…”
Section: Spin-orbit Coupling In Wurtzite Semiconductors and Other Matmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, all the linear in k terms are of the Rashba-type, 12 which makes them indistinguishable in experiments. Indeed, experiments revealed that the spin-orbit coupling is dominated by the Rashba-type spin-orbit coupling, where no effect that signals spin-orbit coupling of the form of (k x σ x − k y σ y ) was observed [247,[256][257][258][259][260]. The measured Rashba parameter lies in the range of 0.6 to 8 × 10 −12 eV m various conditions [251][252][253][254][261][262][263][264][265][266][267][268].…”
Section: Spin-orbit Coupling In Wurtzite Semiconductors and Other Matmentioning
confidence: 90%
“…Moreover, from the first term in Eq. (256), one can see that the light hole spin-up states can be directly mixed with the heavy hole states by S and R, but the mixing between light hole spin-up states and light hole spin-down states has to be mediated by the heavy hole states. All the mixing is related to the confinement.…”
Section: Hole Spin Relaxation In P-type (001) Gaas Quantum Wiresmentioning
confidence: 97%
“…HDP has been observed on many systems with SOC2627. As a system with strong SOC, there could be additional sources of HDP in the Bi 2 Se 3 flakes.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, optical injections of spinpolarized charge currents have been demonstrated through quantum interference in bulk GaAs 16 and by spin photogalvanic effect in several structures including GaAs quantum wells ͑QWs͒, [17][18][19] InAs QWs, 20 Si/Ge QWs, 21 and AlGaN/ GaN superlattices. [22][23][24][25] These spin currents are generated optically, without applying any external electric fields. However, in each of these studies currents were detected not by optical techniques but by measuring steady-state voltage [16][17][18][19][20][21][22][23][24][25] caused only by the charge component of the currents.…”
mentioning
confidence: 99%
“…[22][23][24][25] These spin currents are generated optically, without applying any external electric fields. However, in each of these studies currents were detected not by optical techniques but by measuring steady-state voltage [16][17][18][19][20][21][22][23][24][25] caused only by the charge component of the currents. Therefore, not only has the degree of spin polarization of these photogenerated currents not measured but, strictly speaking, even the existence of a spin component of these currents has not been experimentally demonstrated since spin polarized carriers do not necessarily carry a spin polarized current.…”
mentioning
confidence: 99%